2020
DOI: 10.1093/aje/kwaa190
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival Among Chemotherapy-Naive Patients With Castration-Resistant Prostate Cancer Under Abiraterone Versus Enzalutamide: A Direct Comparison Based on a 2014–2018 French Population Study (the SPEAR Cohort)

Abstract: Abiraterone acetate (ABI) and enzalutamide (ENZ) are considered as clinically relevant comparators among chemotherapy-naïve castration-resistant prostate cancer patients. No clinical trials comparing overall survival (OS) of ABI to ENZ in a head-to-head approach have been published so far. A few observational studies with lack of power suggested a potential benefit of ENZ. Among chemotherapy-naïve castration-resistant prostate cancer patients, we used the French National Health Data System (‘SNDS’), to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
3
18
1
Order By: Relevance
“…Similar analyses of data from a similar, smaller group of veterans with prostate cancer support our ndings that enzalutamide is associated with longer treatment duration and reduced risk of death versus abiraterone, particularly among patients who only received one treatment for mCRPC (18). Additionally, a French study found improved survival with enzalutamide versus abiraterone in a multivariable model with a similar HR of 0.90 (19). Our study improves on prior studies by comparing abiraterone and enzalutamide treatment during a time period when the drugs had the same FDA indications, includes multiple analyses that adjust for a range of patient factors including both a Cox proportional hazards and a propensity score matched model, and includes patients who received prior chemotherapy, which was commonly used for hormone sensitive prostate cancer.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar analyses of data from a similar, smaller group of veterans with prostate cancer support our ndings that enzalutamide is associated with longer treatment duration and reduced risk of death versus abiraterone, particularly among patients who only received one treatment for mCRPC (18). Additionally, a French study found improved survival with enzalutamide versus abiraterone in a multivariable model with a similar HR of 0.90 (19). Our study improves on prior studies by comparing abiraterone and enzalutamide treatment during a time period when the drugs had the same FDA indications, includes multiple analyses that adjust for a range of patient factors including both a Cox proportional hazards and a propensity score matched model, and includes patients who received prior chemotherapy, which was commonly used for hormone sensitive prostate cancer.…”
Section: Discussionsupporting
confidence: 82%
“…Large data analyses of real-world treatment can inform clinical practice in situations of clinical equipoise and identify potential differences in survival among patients who are not routinely included in clinical trials. Prior studies showed bene t of enzalutamide over abiraterone using real-world data from the VHA (18) and a French cohort (19). However, analyses of patients with comorbidities such as cardiovascular disease and diabetes have not been performed and these sub-groups could de ne which patients bene t from careful selection of ARTA therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Tagawa et al reported that ENZ patients had a 16% lower risk of death (adjusted HR = 0.84; 95% CI, 0.76–0.84; p = 0.0012), with increased median OS (29.63 months vs. 25.87 months) [ 32 ]. Scailteux et al suggested a 10% improved OS with ENZ versus AA (34.2 m vs. 31.7 m, HR 0.90, 95% CI 0.85–0.96) [ 33 ]. Demirci et al found longer radiographic progression-free survival (rPFS) and OS with ENZ (15 m vs. 7 m, p < 0.001 and 29 m vs. 16 m, p = 0.027), alongside more frequent PSA decline greater than 50% ( p = 0.020) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, ENZ is associated with more favorable survival and disease control. Three studies demonstrated better survival following ENZ compared with AA [ 32 , 33 , 34 ]. Several studies showed a similar trend but did not reach statistical significance, primarily due to low sample sizes during subgroup analyses performed to exclude confounding patient factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study, comparing them in the first line of mCRPC showed that ENZA had better mOS compared to AA (HR 0.90, 95% CI 0.85, 0.96; mOS, 31.7 months for AA and 34.2 months for ENZA) [10]. A metaanalysis by Wang et al [11] concluded that ENZA was associated with a higher PSA response rate compared to AA in patients with mCRPC, and no significant difference was found in terms of toxicity profiles.…”
Section: Introductionmentioning
confidence: 99%